1992
DOI: 10.1172/jci115657
|View full text |Cite
|
Sign up to set email alerts
|

Persistent defective coupling of dopamine-1 receptors to G proteins after solubilization from kidney proximal tubules of hypertensive rats.

Abstract: The natriuretic effect of dopamine-1 (DA-1) agonists is reduced in spontaneously hypertensive rat (SHR), partly because of defective DA-1 receptor-adenylate cyclase (AC) coupling in renal proximal convoluted tubules. To investigate this defective coupling, DA-1 dopamine receptors from renal proximal tubules were solubilized and reconstituted into phospholipid vesicles.The binding of DA-1-selective ligand 1125I1SCH 23982 was specific and saturable, with no differences in receptor density or Kd between SHR and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 33 publications
(32 reference statements)
2
20
0
Order By: Relevance
“…In addition to its role in maintaining sodium homeostasis under normal conditions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), defects in the renal paracrine/ autocrine DA axis have been demonstrated and postulated to contribute to certain forms of polygenic hypertension in both rodents (77)(78)(79)(80)(81)(82)(83)(84)(85)(86) and humans (87)(88)(89)(90)(91)(92). In the proximal tubule where 50 -60% of NaCl and water is reabsorbed, DA inhibits the basolateral membrane Na ϩ ,K ϩ -ATPase (34 -38), which is the primary driving force for transepithelial Na ϩ absorption.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in maintaining sodium homeostasis under normal conditions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), defects in the renal paracrine/ autocrine DA axis have been demonstrated and postulated to contribute to certain forms of polygenic hypertension in both rodents (77)(78)(79)(80)(81)(82)(83)(84)(85)(86) and humans (87)(88)(89)(90)(91)(92). In the proximal tubule where 50 -60% of NaCl and water is reabsorbed, DA inhibits the basolateral membrane Na ϩ ,K ϩ -ATPase (34 -38), which is the primary driving force for transepithelial Na ϩ absorption.…”
Section: Discussionmentioning
confidence: 99%
“…In two experimental models of hypertension, spontaneously hypertensive rats (SHR) and Dahl salt sensitive rats, defective coupling of dopamine to adenylate cyclase activation has been noted (49)(50)(51)(52)(53). In hypertensive humans, both defective renal dopamine production in response to salt loading and decreased proximal tubule responsiveness to dopamine have also been reported (54).…”
Section: Discussionmentioning
confidence: 99%
“…83,89,90 We and others have performed extensive studies to investigate the site(s) of defect in the D 1 -like receptor system in the SHR. 4,39,[91][92][93] Because proximal tubular dopamine receptors (D 1 -like receptors) contribute to 60% of the sodium excretion under acute volume expansion, a phenomenon that is impaired in SHR, studies have been conducted on the D 1 -like receptor system in the proximal tubules to investigate the site of impairment. In 1989, Kinoshita et al 4 reported that D 1 -like receptor agonists stimulated adenylyl cyclase activity to a lesser extent in the proximal tubules of SHR compared with normotensive WKY.…”
Section: Spontaneously Hypertensive Ratsmentioning
confidence: 99%